2018
DOI: 10.1016/j.btre.2018.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the ethanol tolerance for wild and mutant Synechocystis strains by flow cytometry

Abstract: HighlightsFlow cytometry was used to evaluate the effect of ethanol on Synechocystis strains.The three Synechocystis strains behaved differently in the presence of ethanol.UL 004 and UL 030 were more tolerant to the presence of ethanol than the WT strain.The most efficient ethanol producer (UL030) was also the most tolerant to ethanol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 39 publications
(67 reference statements)
0
33
0
Order By: Relevance
“…Furthermore, it has been shown that the catalytic activity of pdc ZM is a limiting factor, as the optimal molar ratio between pdc:adh would be 1:2.5 but is 1:30 to 1:40 so far [72]. [32] This result is supported by the fact that a double integration to increase the copy number of the genes further increased the ethanol yield. However, no significant difference in growth and ethanol production capacity was observed between a strain with double integration of the whole pdc ZM -adh SYN construct and a strain harbouring two copies of pdc ZM and one copy of adh SYN [31,72].…”
Section: Bioethanol Production In Cyanobacteriamentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, it has been shown that the catalytic activity of pdc ZM is a limiting factor, as the optimal molar ratio between pdc:adh would be 1:2.5 but is 1:30 to 1:40 so far [72]. [32] This result is supported by the fact that a double integration to increase the copy number of the genes further increased the ethanol yield. However, no significant difference in growth and ethanol production capacity was observed between a strain with double integration of the whole pdc ZM -adh SYN construct and a strain harbouring two copies of pdc ZM and one copy of adh SYN [31,72].…”
Section: Bioethanol Production In Cyanobacteriamentioning
confidence: 99%
“…Therefore, alternative methods like for example different stripping methods need to be investigated [12,33]. Currently, so far the highest productivity of 0.285 g L −1 d −1 in cyanobacteria was achieved by Lopes da Silva et al [32] and the highest ethanol titre of 5.50 g L −1 in 26 days was reached by Gao et al [31]. Compared to the other model organisms like S. cerevisiae or E. coli with 130 g L −1 in 65 h and 20.7 g L −1 in 96 h, respectively, there is still a big step to be made in cyanobacteria [21].…”
Section: Comparison Of Ethanol Productionmentioning
confidence: 99%
See 3 more Smart Citations